A new fast radio burst in the data sets containing the Lorimer burst. (20th February 2019) - Zhang, S-B; Hobbs, G; Dai, S; Toomey, L; Staveley-Smith, L; Russell, C J; Wu, X-F
Abstract: We report the discovery of a new fast radio burst (FRB), FRB 010312, in archival data from a 1.4 GHz survey of the Magellanic Clouds using the multibeam receiver on the Parkes 64-m-diameter radio telescope. These data sets include the Lorimer burst (FRB 010724), which it pre-dates and which we also re-detect. The new burst has a much higher dispersion measure of 1187 cm −3 pc. The burst is one of the broadest found to date, the second earliest FRB known, and the ninth FRB discovered with a dispersion measure larger than 1000 cm ^-3 pc. Our discovery indicates that there are likely to be more burst events still to be found in the existing Parkes data archive.